Associations of lifestyle factors and anthropometric measures with repeat PSA levels during active surveillance/monitoring. - Burton, A; Martin, R; Donovan, J; Lane, J; Davis, M; Hamdy, F; Neal, D; Tilling, K (2012)
BACKGROUND: Assessment of prostate-specific antigen increase with time (PSA growth) is a fundamental component of active surveillance among men with localized prostate cancer. Factors that influence PSA growth, however, are unclear. We evaluated associations of anthropometric and lifestyle factors with age-related PSA growth. METHODS: Repeat PSA measures from 404 men, aged 50 to 69 years, with localized prostate cancer undergoing active monitoring were obtained. From log(PSA) measures, age-specific multilevel mixed effect linear models were developed to predict PSA at age 50 years and yearly increase in postdiagnosis PSA. Baseline anthropometric measures, alcohol consumption, occupational class, smoking status, and physical activity were added to the model as covariates. RESULTS: The median number of repeat PSAs was 13 (range, 2-40), and the mean duration of follow-up was 4.8 years (SD, 2.3). The basic model of age-related PSA growth in men with localized prostate cancer estimated a mean PSA at age 50 of 3.95 ng/mL [95% confidence interval (CI): 3.55 to 4.39] and a yearly increase of 8.50% (95% CI: 7.90% to 9.10%). PSA at age 50 years was 2.1% lower per unit increase in weighted exercise score (95% CI: -3.3 to -0.8), 5.3% lower per 5 cm increase in height (95% CI: -9.4 to -1.1), and 24.5% higher (95% CI: 4.0 to 49.1) in current smokers than never smokers. Similar associations with PSA growth were seen. CONCLUSION: Smoking and exercise are modifiable lifestyle factors that may be associated with PSA levels in men with localized prostate cancer undergoing active monitoring/surveillance. IMPACT: These factors may be useful in understanding etiology of progression.